2017
DOI: 10.1007/s13187-017-1172-0
|View full text |Cite
|
Sign up to set email alerts
|

Health Beliefs Associated with the Follow-Up of Pap Smear Abnormalities Among Low-Income Women in Medellín, Colombia

Abstract: The purpose of the study was to explore variables of the health belief model in relation to the follow-up of abnormal Pap smear among low-income women in Medellín, Colombia. Eight focus groups (62 women) were conducted according to age groups (25-45 and 46-69 years). The data were analyzed using content analysis. The participants perceived themselves as vulnerable, recognized the severity of the disease in terms of both its emotional and physical consequences, perceived the benefits of the follow-up, and menti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…similar to our findings, Park et al [31], reported that after education, the experimental group had a higher score of perceived benefits of Pap smear test. Garces-Palacio et al [32], and Jirojwong et al [33], argued that there was a positive relation between the perceived benefits and the rate of doing Pap smear tests. According to the HBM, an individual performs an action when they rationally find its benefits more than the barriers.…”
Section: Discussionmentioning
confidence: 99%
“…similar to our findings, Park et al [31], reported that after education, the experimental group had a higher score of perceived benefits of Pap smear test. Garces-Palacio et al [32], and Jirojwong et al [33], argued that there was a positive relation between the perceived benefits and the rate of doing Pap smear tests. According to the HBM, an individual performs an action when they rationally find its benefits more than the barriers.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to other studies that showed women generally need approval or support from their partners to access health services. [6,15] Similar to above, outreach and counseling interventions that incorporate stigma reduction could have a positive impact on partner support.…”
Section: Discussionmentioning
confidence: 94%
“…This finding was similar to that in other studies, which found that lack of social support was a potential barrier to follow-up care. [15,16] Lack of social support was a clear barrier among LTFU women and a clear proposed facilitator to treatment among all women. Using social support as a facilitator for treatment seeking has been proposed in other studies in the past, supporting this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, Park et al [22],reported that after education, the experiment group had a higher score of perceived benefits of Pap test. Garces-Palacio et al [23], and Jirojwong et al [24], argued that there was a positive relationship between the perceived benefits and the rate of doing pap tests. According to the HBM, an individual performs an action when they rationally find its benefits higher than the barriers.…”
Section: Discussionmentioning
confidence: 99%